Efficient Constant Modulus Based Carrier Frequency Offset Estimation for CO-OFDM Systems - Muyiwa B. Balogun; Olutayo O. Oyerinde; Fambirai Takawira (IEEE Photonics Journal)
This paper proposes a blind carrier frequency offset (CFO) estimation method for coherent optical orthogonal frequency division multiplexing (CO-OFDM) systems, using constant modulus signaling. The proposed scheme is based on a robust cost-function, which deviates from the common assumption that the channel frequency response slowly varies either in time or frequency domain. The proposed method adopts a cost-function similar to the Godard's method for blind channel equalization. Using Monte Carlo simulations, the proposed method is shown to offer a superior performance compared to prominent existing methods, in a practical optical link scenario. Also, we show that the proposed cost-function can be approximated and expressed in a closed-form in such a way that the CFO estimate is obtained using only three trial values.